Performance analysis in the coal bagging plant of Garp Lignite Corporation. Issue 1 (31st December 2016) - Bahşiş, Mehmet Nuri; Kasap, Yaşar
Abstract: Companies can contribute to a country's economy by means of efficient production in each of their units. The aim of this study was to examine the change in operational performance of the coal bagging plant of Garp Lignite Corporation in Turkey using the Malmquist total factor productivity index. The results showed that there was a decrease in the productivity of the bagging plant. This decrease could be due to the rapid growth of the market share of natural gas in heating and energy in recent years, the reduced demand for lignite, overuse use of energy as a result of the necessity to keep the plant active even when no bagging is performed, the current labor-intensive bagging process, and the difficulty in working continuously with qualified staff hired depending on the demand for coal. In conclusion, it is recommended that a fully automated coal bagging plant be built in the corporation.